2010
DOI: 10.1177/183693911003500203
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Assessing Social and Emotional Competence and Wellbeing in Young Children

Abstract: DEVELOPING POSITIVE SOCIAL and emotional growth and development in young children has always been a fundamental priority of early childhood practitioners. However, with an increasing economic and political focus on the foundational early childhood years, there has been a global push for the measurement of outcomes in early childhood education. This paper reports the findings of a major literature review to examine the assessment of social and emotional competence and wellbeing in young children. The review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 6 publications
1
27
0
3
Order By: Relevance
“…Research has shown that ECEC staff who know children's level of development demonstrate better pedagogical practices. Where staff have knowledge of the level of development of children in specific areas, such as motor development, language development, social development, emotional development and self-regulation, they are better informed to adjust their practices to suit the child's needs (Barblett and Maloney, 2010). There is a range of techniques for child assessment and monitoring, such as subjective judgments, narrative reports of child behaviour, and standardised assessments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research has shown that ECEC staff who know children's level of development demonstrate better pedagogical practices. Where staff have knowledge of the level of development of children in specific areas, such as motor development, language development, social development, emotional development and self-regulation, they are better informed to adjust their practices to suit the child's needs (Barblett and Maloney, 2010). There is a range of techniques for child assessment and monitoring, such as subjective judgments, narrative reports of child behaviour, and standardised assessments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The working relationship depends on human attitudes and behaviour and the quality of the workplace (Kalleberg, Reskin, Hudson, 2000). Building a relationship and tackling conflict is a social competence where a person is focused on creating and strengthening social interaction (Barblett & Maloney, 2011). Working with people is not connected with silence and avoidance of any communication.…”
Section: Role Of Competence At Workmentioning
confidence: 99%
“…All children need a healthy and nurturing family environment (Republic of South Africa, 2013). For example, research by Barblett and Maloney (2010) indicates that physical health and emotional competencies are vital for the healthy development of children. However, if children continuously experience lack with regards to basic needs and relational health, then an increase of risks is likely (Van Schalkwyk & Wissing, 2010).…”
Section: Problem Statementmentioning
confidence: 99%